Prevalence and factors associated with not receiving the booster dose of the COVID-19 vaccine in adults in Latin America and the Caribbean - Urrunaga-Pastor, Diego (2022)
“Background: Booster doses have been described as effective in reducing hospitalizations and deaths from the new variants. However, its coverage is heterogeneous in Latin America and the Caribbean (LAC), one of the regions most affected by the pandemic. We aimed to assess the factors associated with not receiving a coronavirus disease 2019 (COVID-19) vaccine booster dose in adults from LAC. Methods: We analyzed a secondary database compiled by the University of Maryland and Facebook assessing the global impact of COVID-19. We included Facebook users over 18 years of age who resided in LAC and responded to the survey between February 13, 2022, and March 14, 2022. We evaluated sociodemographic characteristics, comorbidities, food, and economic insecurity, mental health, and vaccination-related practices. We calculated crude (cPR) and adjusted (aPR) prevalence ratios with their respective 95% confidence intervals (95%CI). Results: The sample included 154,841 adults from 20 LAC countries. 33.7% (n = 46,459) reported not receiving the COVID-19 booster vaccine. Being under 75 years old, having a college, high school, pre-university, primary, or lower education, having no or 1 to 2 comorbidities, living in a town, having food insecurity, depressive symptoms, and having had COVID-19, were associated with a higher prevalence of not receiving the booster dose. In contrast, being female or non-binary and having anxiety symptoms were associated with a lower prevalence of not receiving the booster dose. Conclusions: Approximately three out of 10 adults surveyed in LAC reported not having received the booster vaccine. Authorities must design campaigns that promote receiving a booster dose considering the factors found.“